Statistical modeling approach for minimizing stresses developed in bolted rail joint - U.G. , Piyush; Gupta , Sanjay (Journal of Production Engineering, 2023)
The paper aims at formulating a statistical model for minimizing the Stresses developed in the bolted rail joint by the variation of different parameters like – distance between the sleepers, Speed of train, Total load on the train, Placement of the rail joint and finding out the optimum values of the parameters to minimize the stress value. An equation capable of predicting value of stress, for any given value of the parameters is formulated. A series of experimental values were obtained from ANSYS by Finite element analysis of the 3D model of rail joint prepared in SolidWorks. Verification of the prepared 3D model was done mathematically. A full 24 factorial experiment approach has been adopted to study the interaction among the parameters. Design-Expert® statistical package has been used and the formulated model is based on Analysis of Variance (ANOVA).